Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Let a be the first term and d be the common difference of given AP then
     pth term = q
     qth term=p

subtracting equ 2 from 1
            d= -1
putting d = -1 in equ 1 , we get
       a+(p-1)-1 =q
                  a   = (p+q-1)

 nth term = a+(n-1)d

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts